Clinically suspected fibrocartilaginous embolism: a case report and literature review. (3rd April 2022) - Ke, Wencan; Chen, Chao; Li, Shuai; Wang, Bingjin; Lu, Saideng; Yang, Cao
Abstract: Spinal cord infarction (SCI) occurs rarely and is characterized by abrupt onset of neck or back pain and neurologic deterioration. Fibrocartilaginous embolism (FCE) of the spinal cord is a rare but possible cause of acutely progressive spinal cord symptoms. Here, we report the case of an older woman who developed acute paraplegia with SCI on the 10th day after thoracic spine surgery. Although definitive FCE diagnosis can be confirmed only histologically, the characteristic clinical and radiological features were highly suggestive of FCE. Furthermore, 40 clinically suspected cases of FCE are reviewed.